Conference Report: Connecting strategies on dried blood spots. (November 2010) - Abbott, Richard; Smeraglia, John; White, Stephen; Luedtke, Silke; Brunet, Leonarda; Thomas, Elizabeth; Globig, Suzanne; Timmerman, Philip
The European Bioanalysis Forum is a non-profit organization comprised of European pharmaceutical companies (25 members to date). Their activities focus on bringing together managers and scientists in the broad field of bioanalysis to discuss topics related to science, process and regulations. There has been much interest over the past few years in the potential application of dried blood spots as an alternative to traditional plasma collection in pharmacokinetic studies. The success of the technique has been highlighted by several companies. We know that seven of the European Bioanalysis Forum member companies are using dried blood spots intensively and that 22 out of 25 companies are using it or plan to use it very soon, initially in nonregulated studies. However, most companies have less than 1 year of experience with dried blood spots and, beyond the scientific merit, it is less clear just how the technique is perceived by key client groups, such as toxicology, clinical and regulatory authorities. The objective of this symposium was to bring together representatives from all of these client groups as well as a broad bioanalytical audience to discuss the various perspectives on dried blood spots and to try to provide answers to potential issues that still remain. The symposium included sessions on dried blood spots in the nonregulated environment, toxicology and regulatory/QA perspectives, clinical use and bioanalytical applications and tools. There was plenty of time for discussion within the program in tutorials, poster and break-out sessions and the degree of delegate participation reflected the high level of engagement with the topic. A total of 190 delegates attended from more than 80 organizations. In addition to 21 oral presentations, more than 20 posters were presented and there was a vendor exposition of ten sponsor companies.